RAGAM METODE PENYULUHAN PEMBANGUNAN MELALUI PEMBERDAYAAN MASYARAKAT PELAKU AGRIBISNIS PADA POKLAHSAR BATUANG SRIKANDI NUSANTARA - Sultani; Ahmad Fachri (Jurnal Media Akademik (JMA), 2024)
Development in all sectors continues to be encouraged, including in the agribusiness sector. One of the efforts to develop the agribusiness sector is through development extension in community empowerment which aims to realize the independence of agribusiness actors. There are many types of development outreach methods, especially in community empowerment efforts. Mardikanto in his book entitled "Agricultural Development Extension" states that there are 13 types of development extension methods. In this research, the thirteen types of extension methods will be analyzed regarding development outreach carried out by the NGO Human Initiative West Sumatra on the empowerment of agribusiness actors by Poklahsar Batuang Srikandi Nusantara in Bungus Teluk Kabung District, Padang City. This research was conducted through deep interviews with key informants. This research was analyzed qualitatively by comparing previous literature. The research results show that there are 10 types of extension methods applied by the West Sumarera NGO Human Initiative, including: key individual method; correspondence; anjangkarya-anjangsana; demonstration; meeting; public meeting; exhibition; film; print media; and campaigns. Meanwhile, the kelompencapir method, performances and radio cassettes have not been implemented. The various methods used in community empowerment must also be adapted to the beneficiary community. So that the goal of development extension in empowering the community to realize independence can be achieved